Timing of delamination of biodegradable temporizing matrix prior to cultured epidermal autografting in burn reconstruction: A case report with literature review - Jeremy T. Joseph; Kristina M. Crawford; Ronnie N. Mubang; Jun Yao; J. Blair Summitt; Salam Al Kassis (Elsevier, 2022)
Background: For extensively burned patients in whom donor sites for skin coverage are scarce, cultured epidermal autografting (CEA) is a reliable method for developing tissue coverage. A biodegradable temporizing matrix (BTM) can be applied for wound bed temporization while CEA is being manufactured. This temporizing matrix allows for the integration of vascular tissue supporting a neodermis onto which a skin graft can be applied. Delamination of the sealing membrane overlying this neodermis is required before skin grafting. CEA manufacturer guidelines suggest wound bed preparation occur one to two days prior to CEA grafting, and traditional practice amongst burn surgeons, including at our institution, is to delaminate BTM the day before CEA placement. However, optimal timing of delamination prior to CEA has not been investigated and variability in this practice exists. Methods: In this case report, we compare BTM delamination 24 h prior versus immediately before CEA placement in a patient with 75% total body surface area burns whose wounds were covered with BTM and subsequently treated with CEA. The "take" of autograft at two sites that were delaminated in a delayed versus immediate fashion were compared. Results: The BTM from the patient's anterior trunk was delaminated a day prior to CEA placement, while his anterior left leg BTM was delaminated with immediate CEA placement. On day 13 after CEA placement, we observed 100% and 90% take at the anterior torso and anterior left leg, respectively. At 1 and 5 months after CEA placement, the anterior left leg was also found to have complete graft take. Conclusion: Although the reconstruction site where BTM delamination with delayed CEA placement seemed to initially demonstrate minor improvement in skin graft take in the early post-operative period in this patient, the ultimate outcome was complete graft take at both sites without morbidity regardless of the delayed versus immediate approach. If similar outcomes between these approaches are confirmed in prospective studies, broader use of immediate CEA placement after BTM delamination may reduce the number of operative cases, overall operative time, hospital length of stay, and overall costs while providing expeditious care of the extensively burned patient.